On the approximate solution of nonlinear singular integral equations with positive index - S. M. Amer (International Journal of Mathematics and Mathematical Sciences)
This paper is devoted to investigating a class of nonlinear singular integral equations with a positive index on a simple closed smooth Jordan curve by the collocation method. Sufficient conditions are given for the convergence of this method in Holder space.